Ragged coast, rugged coves labor, culture, and politics in southeast Alaska canneries - Purvis, Diane J. (University of Nebraska Press, 2021)
"Ragged Coast, Rugged Coves explores the untold story of cannery workers in southeast Alaska from the Russian era through the Cold War, particularly how making a living was pitted against the economic realities of the day"--